Magnet Temperature Estimation Methodology by Using Magnet Flux Linkage Observer for Variable Leakage Flux IPMSM - Kato, Takashi; Sasaki, Kensuke; Diego Fernandez Laborda; Daniel Fernández Alonso; David Díaz Reigosa; 加藤 崇; 健介, 佐々木 (IEEJ JOURNAL OF INDUSTRY APPLICATIONS, 2020)
This paper presents a novel methodology of magnet temperature estimation using a magnet flux linkage observer for a Variable Leakage Flux Interior Permanent Magnet Synchronous M (VLF-IPMSM), whose parameters vary depending on load current conditions. The magnet temperature estimation algorithm consists of a Gopinath-Style flux observer, magnet flux linkage observer, and magnet temperature estimator based on the look-up table. The estimation accuracy is evaluated on d-q current plane by using both a behavior model of JMAG-RT and a control model of MATLAB Simulink. Then it is shown that the proposed methodology can be applied to a VLF-IPMSM for magnet temperature estimation.